How University Students Assess Their Water Skills - Goran Dimitrić; Milorad Jakšić; Filip Sadri; Dorica Šajber; Tanja Kaurin; Nataša Zenić; Elena Tabakova (Frontiers Media S.A., 2022)
The aim of this study was to determine the gender differences between students' actual and perceived water abilities, how respondents assess risk in the described situations, and whether there are gender differences for those situations. The cross-sectional study was conducted on 150 students aged 19-20 years (males, n = 88; females, n = 62) from the faculty of sport and physical education, University of Novi Sad. Using calculated frequencies and estimates, students' self-assessment and actual measures of their swimming and survival skills and their perceived risk of drowning are described. Based on the results, Mann-Whitney U tests were applied. The differences between independent variables (gender) were analyzed according to dependent measures (water competency). To determine the significance of the relationship between actual and perceived skills, Spearman-rank correlation coefficients were calculated. The results of this study confirmed gender differences between students' actual and perceived water abilities, and that the male and female students had inaccurate perceptions of their own perceived and real water abilities. Both male and female students, with high precision, assessed their ability to swim long distances (rs = 0.601; rs = 0.694) just as female students assessed their ability to float (rs = 0.698). Male students greatly overestimated their backstroke swimming, while female students underestimated their ability to dive into the water. Both groups overestimated underwater swimming and underestimated their surface dive skill. Also, there was gender differences between students in assessing the risk for described situations.